Nickel-catalyzed C-H alkylation of indoles with unactivated alkyl chlorides: evidence of a Ni(i)/Ni(iii) pathway - Pandey, Dilip K.; Ankade, Shidheshwar B.; Ali, Abad; Vinod, C. P.; Punji, Benudhar (Chemical Science, 2019)
A mild and efficient nickel-catalyzed method for the coupling of unactivated primary and secondary alkyl chlorides with the C-H bond of indoles and pyrroles is described which demonstrates a high level of chemo and regioselectivity. The reaction tolerates numerous functionalities, such as halide, alkenyl, alkynyl, ether, thioether, furanyl, pyrrolyl, indolyl and carbazolyl groups including acyclic and cyclic alkyls under the reaction conditions. Mechanistic investigation highlights that the alkylation proceeds through a single-electron transfer (SET) process with Ni(i)-species being the active catalyst. Overall, the alkylation follows a Ni(i)/Ni(iii) pathway involving the rate-influencing two-step single-electron oxidative addition of alkyl chlorides.

Achiral and chiral NNN-pincer nickel complexes with oxazolinyl backbones: application in transfer hydrogenation of ketones - Jagtap, Rahul A.; Ankade, Shidheshwar B.; Gonnade, Rajesh G.; Punji, Benudhar (New Journal of Chemistry, 2021)
We describe the synthesis of new NNN-oxazolinyl-pincer nickel complexes and their application in the transfer hydrogenation of ketones. Achiral NNN-ligands, R `(2)-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [((R ` 2-OxNNNEt2))-H; R' = H (3a), R ` = Me (3b)], and chiral ligands, (R)-R `-oxazolinyl-2-C6H4-NH-C(O)CH2NEt2 [(R)-((R `-OxNNNEt2))-H; R ` = Ph (3c), R ` = CH2Ph (3d), R ` = Pr-i (3e), R ` = (CH2Pr)-Pr-i (3f)], were efficiently synthesized. Treatment of these ligands with (DME)NiCl2 afforded the desired amido-pincer nickel complexes, ((R ` 2-OxNNNEt2))NiCl [R ` = H (4a), R ` = Me (4b)] and ((R `-OxNNNEt2))NiCl [R ` = Ph (4c), R ` = CH2Ph (4d), R ` = Pr-i (4e), R ` = (CH2Pr)-Pr-i (4f)], in good yields. All the ligand precursors and nickel complexes were thoroughly characterized by various analytical techniques. The molecular structures of 4a, 4d and 4f were established by X-ray crystallography. The developed nickel complexes were found to be efficient catalysts for the transfer hydrogenation of ketones using (PrOH)-Pr-i as a viable hydrogen source. Enantioselectivity in hydrogenation was not observed with the developed chiral catalysts.

Ni(II)-catalyzed intramolecular C-H/C-H oxidative coupling: an efficient route to functionalized cycloindolones and indenoindolones - Ankade, Shidheshwar B.; Samal, Pragnya Paramita; Soni, Vineeta; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2021)
Nickel(II)-catalyzed intramolecular C(sp(2))-H/C(sp(3))-H and C(sp(2))-H/C(sp(2))-H oxidative couplings in indoles are achieved via chelation assistance. These reactions provide access to biologically relevant five- and six-membered substituted cyclopentaindolones, carbazolones, and indenoindolones in high yields and good chemoselectivity employing an air-stable and defined nickel catalyst, (bpy)Ni(OAc)(2). The oxidative cyclizations proceeded either through a six-membered or an unconventional seven-membered nickelacycle. An extensive mechanistic investigation by experiments and theoretical calculations revealed a facile indole's C(2)-H nickelation and a rate-limiting reductive elimination process. This intramolecular oxidative cyclization operates via a probable Ni(II)/Ni(III) pathway involving single-electron oxidation of nickel without the participation of a carbon-based radical.
Keywords: C-H activation; cycloindolones; indenoindolones; indoles; Mechanism; Nickel; oxidative coupling

Unactivated alkyl halides in transition-metal-catalyzed C-H bond alkylation - Ankade, Shidheshwar B.; Shabade, Anand B.; Soni, Vineeta; Punji, Benudhar (ACS Catalysis, 2021)
Alkylation represents an important organic transformation in molecular science to develop privileged alkylated arenes and heteroarenes. Especially, the direct C-H bond alkylation using unactivated alkyl halides is a straightforward and attractive approach from both the step-economy and chemoselectivity perspectives. Substantial progress has been made in the direct alkylation using primary, secondary, and tertiary alkyl halides along with the methylation and fluoroalkylation. This Review broadly summarizes the transition-metal-catalyzed alkylations of C-H bonds on various arenes and heteroarenes with unactivated alkyl halides until October 2020. On the basis of the substrates utilized for alkylation, the Review is divided into two major sections: alkylation of arenes and alkylation of heteroarenes.
Keywords: (hetero)arenes; Alkylation; C-H activation; transition metals; unactivated alkyl halides

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter

Nickel-catalyzed branch-selective C-H alkylation of indoles and azoles with alkenes: an additive- and solvent-free approach - Ankade, Shidheshwar B.; Banerjee, Shuvajit; Punji, Benudhar (European Journal of Organic Chemistry, 2024)
The development of sustainable protocols for the synthesis of alkylated heteroarenes is crucial owing to their widespread existence in medicinally relevant and bioactive natural products. Herein, we describe an efficient, additive- and solvent-free approach for the regioselective C-H alkylation of indoles and azoles with alkenes using a nickel catalyst, which proceeds through a chelation-assistance strategy. The reaction exclusively provided branched alkylated products with the compatibility of alkyl, alkoxy, fluoro, trifluoromethyl, alkene, cyano, ester, and carbonyl groups. This protocol is applicable to other heteroarenes, such as imidazoles and benzimidazoles, providing the desired alkylated products with exclusive Markovnikov selectivity. The synthetic utility and scale-up of the reaction are demonstrated, and the protocol is in concord with the principles of green chemistry. Alkylation proceeds through facile and reversible C-H nickelation and alkene insertion processes, presumably involving rate-limiting reductive elimination. A straightforward nickel-catalyzed protocol for the C-H alkylation of indoles and azoles is disclosed that proceeds under additive- and solvent-free conditions. The reaction utilizes readily available alkenes as alkylating partners and delivers Markovnikov products with tolerance of sensitive functionalities. image
Keywords: Alkylation; branch selectivity; indoles; Nickel; solvent-free synthesis